2013
DOI: 10.1080/15287394.2013.851632
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Chlorophyllin and Lycopene from Water Spinach Extract on Cytotoxicity and Oxidative Stress Induced by Heavy Metals in Human Hepatoma Cells

Abstract: The purpose of this study was to examine the inhibitory effects of ethanol extract of water spinach (EEWS) containing chlorophyll and lycopene on cytotoxicity and oxidative stress in liver induced by heavy metals. The (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) MTT assay and dichlorofluorescein (DCF) assay were conducted to measure cytotoxicity and inhibition of reactive oxygen species (ROS), respectively. Cytotoxicity was prevented at a concentration of 11.7 mg/L of EEWS. Both sodium copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Melidou et al (2005) found that intracellular binding of iron is responsible for the protection offered by flavonoids against H 2 O 2 -induced DNA damage. On the other hand, complexation of plant extracts with metal ions might diminish the absorption of metal ions leading to chelating and blocking metalmediators generating the ROS (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Melidou et al (2005) found that intracellular binding of iron is responsible for the protection offered by flavonoids against H 2 O 2 -induced DNA damage. On the other hand, complexation of plant extracts with metal ions might diminish the absorption of metal ions leading to chelating and blocking metalmediators generating the ROS (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some researches indicated the fact that phenolic compounds were able to chelate metal ions. On the other hand, complexation of plant extracts with metal ions results in a significant reversal from antioxidant to pro-oxidant properties for the resulting complexes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Among natural antioxidants, phenolic antioxidants are extensively available in plants (50)(51)(52). Effectiveness of antioxidant activity of plant extracts in vitro is probably caused by their ability to act as free radical scavengers (53,54). It has been demonstrated that administration of Borage was protective against Aα-induced memory and antioxidant deficit (6).…”
Section: Discussionmentioning
confidence: 99%